Sounds produced by bottlenose dolphins (Tursiops): a review of the defining characteristics and acoustic criteria of the dolphin vocal repertoire. Issue 4 (3rd July 2020) - Jones, Brittany; Zapetis, Maria; Samuelson, Mystera M.; Ridgway, Sam
ABSTRACT: Bottlenose dolphins make many different sounds that have been recorded and described by researchers for over 60 years. This species, Tursiops truncatus, is arguably the most studied marine mammal. They have the ability to hear and produce sounds over a range of at least 150 kilohertz (kHz). Although the human hearing is limited in bandwidth to less than 20 kHz, dolphin sounds have historically been described as humans perceive them (e.g. whistles, squeals, buzzes, barks, quacks, pops, etc.). Often the same names have been used for different sounds and different names have been used for sounds that are apparently the same. In this review, we try and summarize the dolphin sound literature and provide standardized spectrograms where possible. Our goal is to provide a foundation for future research to build upon by providing a tool for identifying whether a sound has been described before. Novel sound types can then be recognized. Also, we encourage future studies that show when dolphins perceive two sound types as different. Detailed reports linking sound and behaviour are also essential. Only then can we have a complete idea of the dolphin repertoire and begin to understand how they use sound for communication.